The Effect of Leisure Intervention on Occupational Performance and Occupational Balance in Individuals with Substance Use Disorder: A Pilot Study - Majid Farhadian; Malahat Akbarfahimi; Peyman Hassani Abharian; Mitra Khalafbeigi; Farzaneh Yazdani (Occupational Therapy International)
Background and Purpose. Leisure, as an occupation, played a crucial role in promoting individuals’ health and well-being. However, the specific impact of leisure as an intervention for individuals with substance use disorder remains unclear. This pilot study was aimed at investigating the effect of a leisure intervention on occupational performance and occupational balance in individuals with substance use disorder. Methods. The sample for this quasiexperimental pretest–posttest with a two-month follow-up design comprised nine individuals aged between 18 and 55 years, selected using a convenience sampling method. The intervention consisted of a 2-month group leisure participation program, conducted twice a week, followed by a 2-month follow-up period. Primary outcome measures included occupational performance and occupational balance, and secondary outcome measures were leisure participation, quality of life, and drug craving. Outcome measures were assessed three times: preintervention, postintervention, and after the follow-up period. The outcome measures included the Canadian Occupational Performance Measure (COPM), Occupational Balance Questionnaire-11 (OBQ11), Nottingham Leisure Questionnaire (NLQ), 36-Item Short-Form Health Survey (SF-36), and Desire to Drug Questionnaire (DDQ). Data analysis was performed using the Friedman test and Wilcoxon signed-rank test as a post hoc procedure, with a significance level set at 5%. Results. The findings showed significant improvements in participants’ occupational performance in postintervention and follow-up assessments (p<0.01, r=0.59) and better occupational balance from pre- to postintervention (p<0.01, r=0.59) and after the follow-up period (p<0.01, r=0.60). Furthermore, significant enhancements were observed in leisure participation, quality of life, and a reduction in drug craving. Conclusion. The findings indicate that leisure intervention positively impacted both occupational performance and occupational balance, suggesting its potential as a beneficial therapeutic approach for individuals with substance use disorder. Additional research is warranted to delve deeper into and validate the effectiveness of leisure intervention within this specific population.